English - Đogatović, Nebojša; Račić, Vladimir; Potkonjak, Ernesta; Milićević, Miloš; Abdulaj, Dajana; Kozomara, Bojan (Scripta Medica, 2020)
Background/Aim: Intravitreal drug injection cause an increase in intraocular pressure (IOP). The increase in IOP is directly proportional to the volume of drug injected into the eye and inversely to the vitreal reflux. The mixture of fluid, presents as a subconjunctival bleb, composed of vitreous and injected drug is called vitreal reflux. In this study changes in IOP after intravitreal injection of bevacizumab in relation to the vitreous regurgitation were observed.Methods: This prospective study involved 50 patients (57 injections). Bevacizumab was administered intravitreally at a dose of 1.25 mg/0.05 mL. According to the type of disease, patients with diabetic macular oedema, proliferative diabetic retinopathy, age-related macular degeneration, retinal vein occlusion, choroidal neovascularisation and central serous chorioretinopathy were included. They were divided into two groups – the first one without vitreal reflux and the second one with vitreal reflux. IOP values were measured at baseline, right after drug application and 20 min thereafter.Results: The reference value range of IOP values were 10-21 mmHg and so were the average baseline values in both experimental groups of patients (15.81 ± 3.50 mmHg). In the experimental group without reflux post application mean values of IOP at 0 and 20 min were 50 ± 9.65 and 18.54 ± 5.06 mmHg, respectively. In the experimental group with reflux post application mean IOP values after 0 and 20 min were 36 ± 8.68 mmHg and 18.91 ± 4.82 mmHg, respectively.Conclusions: Following intravitreal bevacizumab application, a significant increase in IOP occurs. After 20 minutes the IOP values spontaneously decreased below 25 mmHg in both groups and there was no significant difference in comparison with the baseline values. Vitreus reflux is a major factor in short-term post-injection IOP elevation, but not from the longer-term perspective.